Valence of Temporal Self-Appraisals: A Comparison Between First-Person Perspective and Third-Person Perspective - Yue, Caizhen; Long, Yihong; Ni, Chaomei; Peng, Chunhua; Yue, Tong (Frontiers in Psychology, 2021)
Mental Time Travel is one of the most remarkable achievements of mankind. People perceivepast self,present self andfuture self as a continuous unity; On the other hand, people have the ability to distinguish among the three types of temporal selves because thereare different representations of them. In this study, we used an adapted temporal self-reference paradigm to explore the processing mechanism of different temporal selves. Temporal self-reference was performed from the first-person perspectivein Experiment 1, and from the third-person perspective in Experiment 2. The results showed that people showed a more positive bias toward future self compared with past self and present self no matter in the first-person perspective or third-person perspective. There was no difference in recognition rate amongpast self,present self andfuture self. Compared with the first-person perspective, present self-processing in the third-person perspective was more abstract and generalized, which may reflect that the third-person perspective has the same distancingfunction. This study can deepen understandings on temporal self-appraisals from different perspectives.